External validation of the traumatic aortic injury score. Issue 1 (28th December 2017) - Bade‐Boon, Jordan; Mathew, Joseph K.; Fitzgerald, Mark C.; Mitra, Biswadev
Abstract : Aim: Traumatic aortic injury (TAI) is a serious complication of blunt chest trauma. The traumatic aortic injury score (TRAINS) is a clinical tool for risk determination, with patients scoring <4 considered low risk. The aim of the present study was to determine the sensitivity of TRAINS on a population of blunt trauma patients with TAI at an Australian major trauma centre. Patients and Methods: Patients diagnosed with thoracic TAI between 2006 and 2014 were identified from an institutional registry. Radiological studies (chest X‐ray) were reviewed, while blood pressure on arrival to hospital was extracted from the registry. Using abbreviated injury scale codes, the presence of the five associated injuries included in the TRAINS model was determined. Results: A TRAINS ≥4 was observed in 28 out of 63 cases, with complete data available (sensitivity = 44.4 per cent; 95 per cent confidence interval: 32.8–56.7), with minimum and maximum possible sensitivities of 42.4 per cent and 47 per cent, respectively, as determined by two‐way sensitivity analysis. Conclusions: This independent external validation of the TRAINS concluded a poor sensitivity for excluding TAI in the blunt chest trauma population. In the absence of reliable predictive tools, a low threshold for thoracic computed tomography imaging and clinical gestalt remain essential tools for the early diagnosis of TAI.